Pengaruh Struktur Kepemilikan, Struktur Aset, dan Kebijakan Dividen Terhadap Kebijakan Hutang dengan Resiko Bisnis Sebagai Variabel Moderasi - Umi, Umi Kalsum (Ali Institute of Research and Publication, 2025)
This study aims to determine the effect of ownership structure, asset structure, and dividend policy on debt policy with business risk as a moderating variable in food and beverage companies listed on the Indonesian Stock Exchange in 2020-2022. This study is a descriptive study with a quantitative approach. The population used in this study were all food and beverage companies listed on the the Indonesian Stock Exchange, totaling 18 companies. The sample used in this study was using saturation sampling techniques consisting of 18 companies. This study uses a data analysis method used is multiple linear regression analysis with the SPSS program. The results of the study indicate that the variables of ownership structure, asset structure and business risk can affect debt policy while dividend policy cannot affect debt policy in food and beverage companies listed on the the Indonesian Stock Exchange. Simultaneously, the variables of ownership structure, asset structure, dividend policy and business risk together affect debt policy in food and beverage companies listed on the Indonesian Stock Exchange. Furthermore, moderating testing was carried out with results stating that business risk cannot influence the relationship between ownership structure variables, asset structure, dividend policy and business risk on debt policy in food and beverage companies listed on the the Indonesian Stock Exchange. Keywords: Ownership Structure, Asset Structure, Dividend Policy, Debt Policy, Business Risk